Hypertensive Crisis in Pregnancy with COVID19: Confirmed with rt-PCR for Nasopharyngeal Swab - Sajith Bandara; Anura Ruwanpathirana; Dhammika Nagodawithana; Samantha Alwis (Case Reports in Obstetrics and Gynecology)
The novel coronavirus has already spread across the geographical borders to 213 countries and self-governing territories. However, the effect of SARS-CoV-2 infection on pregnant mothers is still poorly understood and sparsely documented. Here, we present a case of a primi mother, who presented with diarrheal episode and proceeded to a hypertensive crisis and placental abruption with rt-PCR (nasopharyngeal swab) confirmed for COVID19. SARS-CoV-2 enters and downregulates host cell-bounded enzyme ACE2 (angiotensin-converting enzyme). This activates the renin angiotensin aldosterone mechanism (RAAM). The activation of RAAM plays a pivotal role in the pathophysiology of hypertensive emergencies. Hence, there is a theoretical possibility of hypertensive crisis associated with ACE2/RAAM dysfunction in pregnant mothers who have COVID19. Therefore, close monitoring of blood pressure and early intervention are of paramount importance in anticipating and preventing serious complications related to hypertension in pregnancy in mothers who have tested positive for SARS-CoV-2, especially in this pandemic situation. Emergency hospital admission and urgent care must be afforded to mothers presenting with high blood pressure with the features suggestive of COVID19 as they are at a risk of rapid deterioration.